The Swedish Nuclear Dilemma : Energy and the Environment. - Nordhaus, William D. (Taylor and Francis, 2014)
Renowned economist William Nordhaus has developed many innovative approaches for analyzing complex environmental questions. He applies them to the possible phaseout of nuclear power in Sweden in The Swedish Nuclear Dilemma: Energy and the Environment. While making a major contribution to that debate, this book has value that extends well beyond the Swedish issue, to the careful and well-informed consideration of environmental and energy questions that industrialized nations and developing regions now face. It is essential for anyone interested in nuclear-power issues and climate change. The Sw.